What has helped and hindered the experience of adult males who returned to school - Derganc, Scott (University of British Columbia, 2015)
How adult males experience returning to school has been rarely documented. The present study explored what helped and hindered adult males in their experience as they returned to school via the adult education system and addressed the following question: “What has helped and hindered the experience of adult males who returned to school?” Twelve males, 19 to 49 years of age in British Columbia, Canada who attended the adult education system operated by the Vancouver School Board, were interviewed using the Enhanced Critical Incident Technique (ECIT) (Butterfield et al., 2009). The qualitative analysis of the interviews identified 346 critical incidents and formed eleven helping categories and seven hindering categories for adult males who returned to school. The eleven helping categories included: (1) Teacher Encouragement, Support and Acceptance, (2) Course Schedule, Timetable and Flexibility, (3) Goals, Motivation and Expectations, (4) Acceptance and Belonging, (5) Stability and Support Systems, (6) Autonomy, (7) Teacher Curriculum Presentation and Delivery (8) Personal Growth, Maturity and Self Awareness, (9) Free or Low Cost, (10) Facilities, Location and Classroom Environment and (11) Computer Literacy and Technology. The seven hindering categories were: (1) Education System Based Instability, (2) Health, Emotional Struggles, Rejection and Judgement, (3) Financial, Work and Family Responsibilities, (4) Academic Struggles, Course Design and Delivery, (5) Immigration, Literacy and Cultural Barriers, (6) Lack of Goals, Motivation and Expectations and (7) Facilities, Classroom and Supplies. The results from this study are discussed in relation to implications for theory, practice and future research. === Education, Faculty of === Educational and Counselling Psychology, and Special Education (ECPS), Department of === Graduate